Precipitation concentration index (PCI) a tool to evaluate the distribution of Rainfall, Barishal, Bangladesh - Saha, Sudip (International Journal of Advanced Geosciences, 2020)
The present research work reveals the mean annual rainfall of Barishal is 2087.34 mm for the investigated period. The maximum annual rainfall was 3390 mm in the year of 1960 and minimum annual rainfall was recorded as 1277 mm in the year of 1964. The annual rainfall is inversely correlated with time. The maximum monthly rainfall is recorded in the month of July. The amount of annual rainfall is strongly significantly positively correlated with the monthly rainfall of May, June, July, August and September. In Barishal, the value of skewness for all rainfall data are positive that indicate the data are skewed to the right. The positive value of kurtosis of the eleven months of the year (except July) means a peaked distribution and a negative value in the month of July reveals the flat distribution with the same mean and standard deviation. The annual PCI value is inversely proportional to the annual rainfall. The analyses of seasonal precipitation concentration index (SPCI) reveals that the rainfall is uniformly distributed in summer monsoon whereas the winter rainfall shows the dominance of strong irregularity in precipitation distribution.Â Â